COVID-19: Success Depends on Medical Concepts, Not Political Views - I. Klepikov (International Journal of Coronaviruses, 2020)
An opinion piece argues that coherent medical concepts should guide pandemic response over political narratives. It stresses evidence-based decision-making, transparent risk communication, and iterative learning guided by clinical evidence.
Keywords: COVID-19